The Concept of “Body without Organs” in the Theory of Architecture of the Late 20th Century - Petrushikhina, Svetlana V. (Actual Problems of Theory and History of Art, 2023)
The article considers the reception of the Deleuzian term ‘body without organs’ by Arie Graafland, Ignasi de Sola Morales and Greg Lynn. The listed authors use this concept in different contexts. Ignasi de Sola Moralez employs the notion ‘body without organs’ in order to describe the architectural imagery of the late capitalism. He believes that this Deleuzian term can reveal the invisible mechanisms, by means of which architecture incorporates itself in economic, cultural, and political dimensions of social life. Arie Graafland uses the ‘body without organs’ term as a critical tool to analyze the program of Downtown Athletic Club (DAC) given by Rem Koolhaas in ‘Delirious New York’. Graafland supposes that the DAC program itself could be understood as a ’body without organs’ in architecture. Greg Lynn applies this notion in order to justify his own design strategy, with which he creates ‘blobs’ — flexible topological structures molded by an external force. Hence, such meaning of the architectural ‘body without organs’ implies the projection of a future building in the virtual reality of CAD software. Despite the differences, all authors mentioned above employ the Deleuzian concept of the ’body without organs’ for the same purpose. The use of this term helps them to demonstrate the dependence of the architectural form on external forces.